Study of some blood components of Damascus goats under Aljabal Alakhdar region (Libya) - El-Jarari, Iibrahim; Amaizik, S,; Belgassem, M, (Al-Mukhtar Journal of Sciences, 2007)
24 Damascus goats (11 males and 13 females) at different ages (1.5, 8 and more than 18 months) were used to estimate the effects of age and sex on some blood constituents under hot climates conditions whereas air temperature averaged between 30-35Co. The results showed that studied blood parameters were influenced by age than sex. No significant differences were observed between sex in all studied traits except concentration of total protein, whereas female goats had significantly higher (P < 0.01) by 9.68% in total plasma protein than males. Regarding to age, red blood corpuscles were significantly higher (P < 0.05) in adults than in juveniles. In contrast, white blood corpuscles (p < 0.01) and lymphocytes (P < 0.05) were higher in the juveniles. According to the studied blood metabolites, results indicated that concentrations of blood glucose and total cholesterol were significantly higher (P < 0.01) in juveniles than in adults, while total plasma protein concentration was higher (p < 0.01) in adults. Meanwhile, sex and age interaction were affected significantly the number 0 f white blood corpuscles (p < 0.05), lymphocytes, total plasma protein, blood glucose and total cholesterol concentrations (p < 0.01). The results indicated that the studied blood component values were significantly affected by age than sex under hot climate conditions.